Exposure to Patterned Auditory Stimuli during Acute Stress Prevents Despair-Like Behavior in Adult Mice That Were Previously Housed in an Enriched Environment in Combination with Auditory Stimuli - Enrique Flores-Gutiérrez; Edith Araceli Cabrera-Muñoz; Nelly Maritza Vega-Rivera; Leonardo Ortiz-López; Gerardo Bernabé Ramírez-Rodríguez (Neural Plasticity)
Several interventions have been shown to counteract the effects of stress that may be related to improved neuroplasticity and neuronal activation. In this sense, environmental enrichment (ENR) protects against acute stress and increases neuroplasticity. It has been suggested that the use of patterned auditory stimuli (PAS) may be beneficial in increasing the effectiveness of ENR on disorders related to stress, such as depression and anxiety. Examples of PAS are classical music compositions that have interesting effects at both clinical and preclinical levels. Thus, we analyzed the effects of the exposure to PAS, represented in this study by Mozart’s compositions, during ENR housing for 35 days in adult male Balb/C mice to evaluate depression-associated behavior using the forced-swim test (FST) paradigm with an additional short exposure to PAS. We found that the ENR mice that were exposed to PAS during both housing and behavioral task (ENR + PAS/FST + PAS) show decreased immobility and the number of despair episodes within a higher latency to show the first bout of immobility. Additionally, we found increased neuronal activation evaluated by the identification of activity-regulated cytoskeleton-associated protein- (Arc-) labeled cells in the prefrontal cortex (PFC) in mice exposed to PAS during housing and in the absence or presence of PAS during FST. Moreover, we found increased neuronal activation in the auditory cortex (AuCx) of mice exposed to PAS during FST. Our study suggests that the exposure to PAS during an emotional challenge decreases despair-like behavior in rodents that were previously housed in an enriched environment in combination with auditory stimuli. Thus, our data indicate that the role of the exposure to PAS as an intervention or in combination with positive environment to aid in treating neuropsychiatric disorders is worth pursuing.